1995
DOI: 10.1017/s0952523800009500
|View full text |Cite
|
Sign up to set email alerts
|

Two signals in the human rod visual system: A model based on electrophysiological data

Abstract: In the human rod visual system, self-cancellation of flicker signals is observed at high rod intensity levels near 15 Hz, both perceptually and in the electroretinogram (ERG). This and other evidence suggests that two rod signals are transmitted through the human retina with different speeds of transmission. Here we report a series of flicker ERG recordings from a normal observer and an observer who lacks cone vision. From these results, we propose a quantitative model of the two rod signals, which assumes (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 71 publications
4
46
0
Order By: Relevance
“…To summarize, we used the differences in both spectral and temporal frequency sensitivity of rods and cones in order to distinguish the rod and cone pathway contributions to 15 Hz ERG responses. In accordance with earlier studies [13][14][15]21], we found a minimum in the 15 Hz amplitude curves of the ERG responses to blue and green stimuli. The results provide evidence that only the rod circuit contributes to the ERG responses for flash strengths close to this minimum.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…To summarize, we used the differences in both spectral and temporal frequency sensitivity of rods and cones in order to distinguish the rod and cone pathway contributions to 15 Hz ERG responses. In accordance with earlier studies [13][14][15]21], we found a minimum in the 15 Hz amplitude curves of the ERG responses to blue and green stimuli. The results provide evidence that only the rod circuit contributes to the ERG responses for flash strengths close to this minimum.…”
Section: Discussionsupporting
confidence: 93%
“…This is in contrast to the descriptive model of the primary and secondary rod pathway as developed by Stockman et al [14], who used a fixed time difference of 33.3 ms (180°at 15 Hz) between the two rod pathways for the entire range of flash strengths. This corresponds to the original hypothesis that the 15 Hz minimum is caused by destructive interference of rod pathway responses because they are in opposite phase [7,13,23].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations